Association of rare variants in neurodegenerative genes with familial Alzheimer's disease. Issue 10 (17th September 2020) - Zhang, Weiwei; Jiao, Bin; Xiao, Tingting; Liu, Xixi; Liao, Xinxin; Xiao, Xuewen; Guo, Lina; Yuan, Zhenhua; Yan, Xinxiang; Tang, Beisha; Shen, Lu
Abstract: Objective: To investigate the impact of rare variants underlying neurodegenerative‐related genes to familial Alzheimer's disease (AD). Methods: We performed targeted sequencing of 277 neurodegenerative‐related genes on probands from 75 Chinese AD families non‐carrying causative mutation of dementia genes. Rare coding variants segregated in families were tested for association in an independent cohort of 506 patients with sporadic AD and 498 cognitively normal controls. East Asians data from the Exome Aggregation Consortium (ExAC) were used as a reference control. Results: A novel rare variant, P410S of PLD3 was found in an early‐onset AD family. LRRK2 I2012T, a causative mutation of Parkinson's disease, was identified in another early‐onset AD family. Missense variants in ABCA7 (P143S and A1507T) and CR1 (T239M) were significantly associated with familial AD ( P = 0.005437, 0.001383, 0.000549), a missense variant in TREM2 (S183C) was significantly associated with AD ( P = 0.000396) when compared with the East Asian controls in ExAC database. A non‐frameshift variant in FUS (G223del) was frequent in AD cases and significantly associated with familial AD ( P = 0.008). Interpretation: Multiple rare coding variants of causal and risk neurodegenerative genes were presented in clinically diagnosed AD families that may confer risk of AD. Our data supported that the clinical, pathological, and genetic architectures of AD, PD, and FTD/ALS may overlapping. We propose that targeted sequencing on neurodegenerative‐related genes is necessary for genetically unclear AD families.